Detection of Bartonella species in the blood of veterinarians and veterinary technicians: a newly recognized occupational hazard? - Lantos, Paul M; Maggi, Ricardo G; Ferguson, Brandy; Varkey, Jay; Park, Lawrence P; Breitschwerdt, Edward B; Woods, Christopher W (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2014)
Bartonella species are important emerging pathogens in human and veterinary medicine. In the context of their daily activities, veterinary professionals have frequent animal contact and arthropod exposures. Detection of Bartonella spp. using traditional culture methods has been limited by poor sensitivity, making it difficult to determine the prevalence of infection in this population. We have developed a detection method combining enrichment culture and molecular amplification, which increases testing sensitivity. We performed a cross-sectional study to determine the prevalence of detectable Bartonella spp. in the blood of veterinary personnel and nonveterinary control subjects. Bartonella was detected by enrichment blood culture with conventional PCR followed by DNA sequencing. RESULTS were correlated with epidemiological variables and symptoms. We detected DNA from at least one Bartonella species in 32 (28%) of the 114 veterinary subjects. After DNA sequencing, the Bartonella species could be determined for 27 of the 32 infected subjects, including B. henselae in 15 (56%), B. vinsonii subsp. berkhoffii in seven (26%), B. koehlerae in six (22%), and a B. volans-like sequence in one (4%). Seventy percent of Bartonella-positive subjects described headache compared with 40% of uninfected veterinarians (p=0.009). Irritability was also reported more commonly by infected subjects (68% vs. 43%, p=0.04). Our study supports an emerging body of evidence that cryptic Bartonella bloodstream infection may be more frequent in humans than previously recognized and may induce symptoms. Longitudinal studies are needed to determine the natural course and clinical features of Bartonella infection.